The Challenge of Substituting Sunflower Oil for Imported Palm Oil: Evidence from Tanzania (2018)
Edible oil imports to Africa grew over 10% per year from 2006 to 2015, and accounted for 34% of the continent’s total growth in food imports over this period—the highest share of any food group. In the same period, several African countries experienced a boom in the local production and processing of oil-seeds. The combination of import growth and domestic production booms reveals a gap in the literature on the characteristics of edible oil demand in Africa. We begin to fill this gap by estimating own-price, cross-price, and expenditure elasticities of demand for palm, sunflower, and other edible oils in Tanzania. We apply a QUAIDS model to detailed household level data - focusing on palm and sunflower oil, because for the most part, palm oil is imported and sunflower is domestically produced. Our main finding is a surprisingly low level of substitution between the domestic and imported edible oils. Simulated budget shares from our estimates suggest that a 10% tariff increase on palm oil leads to less than a 0.06% change in the budget share of domestically produced sunflower oil. We identify other potential policy implications from our findings and highlight steps for further research.